A review of the 2-year recurrence rates in laparoscopically resected colorectal malignancies in Hospital Universiti Sains Malaysia - Mohamed, Khairun Nisa' (2018)
Introduction Surgical resection is considered the primary treatment modality in most cases of colorectal carcinoma and achievement of an oncologically-sound resection has been shown to be possible by laparoscopic approach. The hesitation in adopting this method may be because of the steep learning curve and concerns of oncologic safety. A commonly studied measure of oncologic outcome is the recurrence rate which, in colorectal cancer occurs most commonly within the first 2 years post resection. This study aims to compare the 2-year recurrence rates of colorectal cancer cases resected laparoscopically to that reported internationally and to describe clinicopathologic factors that may contribute to the risk of recurrence. Methods This is a retrospective observational study of the patients diagnosed with colorectal cancer who underwent elective laparoscopic colectomy in HUSM from January 2007 to December 2014. All such patients who had a minimum 24-month follow-up and traceable records were included in the study whilst those with concurrent pathologies were excluded. Patients‘ clinicopathological data and follow-up details for 2 years post-surgery was studied. Data was collected in a structured proforma and the survival analysis of which was done using Cox regression formula. The results of data collection and analysis were then compared to results of studies conducted internationally.Results From the period of January 2007 to December 2014, a total of 53 patients underwent elective laparoscopic colectomy for colorectal cancer. A total of thirteen patients were excluded thus, data analysis was performed for 40 patients. The mean age at surgery was 61.5 years. 55% of patients were male whilst 45% were female and 90% of the patients were Malay whilst the remaining 10% were Chinese. Majority of the cases were left sided cancers (95%), 42.5% of whom were cases of anorectal or rectal cancers. There were 4 (10%) patients with Stage I disease, 14 (35%) patients with Stage II disease, 12 (30%) patients with Stage III disease and 10 (25%) patients with Stage IV disease. Five patients had recurrence within 2 years postsurgery resulting in a recurrence rate of 12.5% which was within the range of recurrence rates of 3 to 15.6% reported internationally. The mean time to disease recurrence was 21.2 months with the earliest recurrence occurring at 15 months post-surgery. Based on the simple cox regression formula, those with higher post-operative serum CEA have a higher risk of recurrence of colorectal carcinoma (HR=1.05, 95%CI: 1.00, 1.10, P value=0.04). Other factors such as presence of one or more comorbidities, final T, N or M stage, final group stage, tumour margin clearance, presence of lymphovascular or perineural invasion and presence of neoadjuvant or adjuvant therapy were not significant (P value>0.05) in an increased risk of recurrence within 2 years post-surgery. Conclusion The recurrence rate for laparoscopically resected colorectal cancers done in HUSM is comparable to international standards. A higher post-operative serum CEA suggests a higher risk for recurrence and thus, may be used as an early indicator for recurrence. Although other factors such as disease stage, nodal status and lymph node harvest appeared to have apossible association, none were statistically significant. As we catch on with the rising trend of minimally-invasive surgery, continued effort towards self-audit and research is warranted to improve our surgical outcomes.